The “Super-Fontan” Phenotype: Characterizing Factors Associated With High Physical Performance - Tran, Derek L.; Celermajer, David S.; Ayer, Julian; Grigg, Leeanne; Clendenning, Carley; Hornung, Tim; Justo, Robert; Davis, Glen M.; d'Udekem, Yves; Cordina, Rachael (Frontiers in Cardiovascular Medicine, 2021)
Background: People with a Fontan circulation usually have moderately impaired exercise performance, although a subset have high physical performance (“Super-Fontan”), which may represent a low-risk phenotype. Methods: People with a “Super-Fontan” phenotype were defined as achieving normal exercise performance [≥80% predicted peak oxygen uptake (VO2) and work rate] during cardiopulmonary exercise testing (CPET) and were identified from the Australian and New Zealand Fontan Registry. A Fontan control group that included people with impaired exercise performance (<80% predicted VO2 or work rate) was also identified based on a 1:3 allocation ratio. A subset of participants were prospectively recruited and completed a series of physical activity, exercise self-efficacy, and health-related quality of life questionnaires. Results: Sixty CPETs (“Super-Fontan”, n = 15; control, n = 45) were included. A subset (“Super-Fontan”, n = 10; control, n = 13) completed a series of questionnaires. Average age was 29 ± 8 years; 48% were males. Exercise capacity reflected by percent predicted VO2 was 67 ± 17% in the entire cohort. Compared to the “Super-Fontan” phenotype, age at Fontan completion was higher in controls (4.0 ± 2.9 vs. 7.2 ± 5.3 years, p = 0.002). Only one (7%) person in the “Super-Fontan” group had a dominant right ventricle compared to 15 (33%) controls (p = 0.043). None of those in the “Super-Fontan” group were obese, while almost a quarter (22%) of controls were obese based on body mass index (p = 0.046). Lung function abnormalities were less prevalent in the “Super-Fontan” group (20 vs. 70%, p = 0.006). Exercise self-efficacy was greater in the “Super-Fontan” group (34.2 ± 3.6 vs. 27.9 ± 7.2, p = 0.02). Self-reported sports participation and physical activity levels during childhood and early adulthood were higher in the “Super-Fontan” group (p < 0.05). The total average time spent participating in structured sports and physical activity was 4.3 ± 2.6 h/wk in the “Super-Fontan” group compared to 2.0 ± 3.0 h/wk in controls, p = 0.003. There were no differences in self-reported current total physical activity score or health-related quality of life between groups (p ≥ 0.05). Conclusions: The “Super-Fontan” phenotype is associated with a healthy weight, lower age at Fontan completion, better exercise self-efficacy, and higher overall levels of sport and physical activity participation during physical development.